Strategi Pengembangan Usaha Tani Dalam Meningkatkan Kesejahteraan Ditinjau Dari Perspektif Ekonomi Islam - Pertiwi, Sri Indah; Ilhamy Nst, Muhammad Lathief; Daulay, Aqwa Naser (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
This research focuses on the SWOT analysis of the Sipirok coffee stone business in Situmba Village, Sipirok District, South Tapanuli Regency. This research uses a descriptive research methodology using a qualitative approach. Primary data from coffee business owners was used for research. This research aims to analyze the conditions of the Sipirok coffee stone business in Situmba Village, The results of the research show that the score obtained on the IFAS matrix is ​​3.87, while the score from the EFAS matrix is ​​4.07. This value shows that the Sipirok coffee stone business is in quadrant II, which means that the score shows that the Sipirok coffee stone business is in the village. Situmba, Sipirok District, South Tapanuli Regency, in the SWOT Analysis which was compiled from internal and external factors, resulted in the ST strategy, namely utilizing existing strengths to overcome existing threats. And finally utilizing agricultural extension workers to care for coffee plants in Situmba Village